OVER-TOURISM: THE UNTOLD STORY OF THE RISE OF SUNNY BEACH, BULGARIA - Mincho Slavov; Rety Palupi (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2019)
Coastal tourism destinations around the globe are chasing and face an increase in arrivals. The prevailing paradigm is “the more, the better.” International bodies, national and local governments, and stakeholders are working toward future growth in numbers with little to no attention to the impact of mass tourism on the destination’s image and tourist satisfaction. This paper use case study approach to investigate the phenomenon of over-tourism in the most popular and famous coastal resort in Bulgaria - Sunny Beach, and how current pro-growth policies affect the destination development and the destination image. This research is using qualitative methods, namely analysis of documents, and relevant literature, and observation. Results of the research exposing that the Bulgarian government and the tourism stakeholders are ignoring the existence and impacts of over-tourism. A revision of present strategies, policies, and practices are necessary for assessing the tourism components as time and duration of stay, expenditures, the purpose of visit and destinations carrying capacity. In conclusion, such knowledge may ultimately contribute to addressing over-tourism issues while constructing a more economically, socially and environmentally sustainable destination. Key words: coastal tourism, over-tourism, development policies, Sunny Beach, Bulgaria